1992
DOI: 10.1007/bf00041752
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of species and varieties of four Amaranthus L. species

Abstract: Callus induction, callus growth and organogenetic processes were investigated in hypocotyl and stem cultures of four species of Amaranthus each of which comprised several varieties. Callus formation occurred in almost all the varieties in 100% of explants. The combinations of naphtaleneacetic acid plus benzylaminopurine or 2,4-dichlorophenoxyacetic acid plus Kinetin were very effective in causing callus formation; the results for callus growth in presence of the same growth regulator combinations revealed in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…When a high concentration of auxin (2,4-D) was used in combination with lower concentration of cytokinin (BAP), a low frequency of callus induction was noted (Table 2). Similar reports of 2, 4-D plus kinetin or NAA plus BAP on callus development was observed in Amaranthus by Flores et al (1982) and Bennici et al (1992). When a high concentration of cytokinin was used with a low concentration of auxin, a low frequency of callus induction was noted.…”
Section: Callus Inductionsupporting
confidence: 82%
See 2 more Smart Citations
“…When a high concentration of auxin (2,4-D) was used in combination with lower concentration of cytokinin (BAP), a low frequency of callus induction was noted (Table 2). Similar reports of 2, 4-D plus kinetin or NAA plus BAP on callus development was observed in Amaranthus by Flores et al (1982) and Bennici et al (1992). When a high concentration of cytokinin was used with a low concentration of auxin, a low frequency of callus induction was noted.…”
Section: Callus Inductionsupporting
confidence: 82%
“…In previous research, Bennici et al (1992) studied 4 different species of Amaranthus (A. caudatus, A. hypochondriacus, A. cruentus and A. hybridus) for callus induction, growth and organogenic processes from hypocotyl and epicotyl cultures and found that 5.4 µM of naphthalene acetic Acid (NAA) plus 4.4 µM of benzyl amino purine (BAP) or 2.3 µM of 2,4-dichlorophenoxyacetic acid (2,4-D) plus 2.3 µM of kinetin were the best combinations for callus induction and complete plantlets were obtained from rooted adventitious shoots. Callus production and shoot regeneration from primary callus or hypocotyl explants have been reported by Flores et al (1982), Flores and Teutonico (1986) in A. cruentus, A. hypochondriacus, A. tricolor and by Bagga et al (1987) in A. paniculatus.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…High molecular weight DNA that was also of high quality and purity was extracted for the GBS method using tissue from aseptically grown seedlings. To obtain fresh tissue for the extraction, seeds were sterilized in 5% HgCl 2 for 5 min followed by 5 min rinses in autoclaved water ( Bennici et al, 1992 ). Sterilized seed was then transferred into individual magenta box (Sigma–Alrich Co. LLC), one per genotype containing 100 ml of Murashige-Skoog media with 2 g of sucrose and placed in a growth chamber for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time as the main objective of obtaining regenerants, researchers obtained a callus tisssue. Rapid and intensive callus formation from hypocotyl explants was observed for A. cruentus L. (6 mg/l NAA + 0.1 mg/l BA) and A. hybridus L. (6 mg/l 2.4-D + 0.1 mg/l KIN (Bennici et al, 1992). Arya and colleagues chose A. paniculatus L. as an object of research.…”
Section: Achievements In Regeneration Of Amaranthus L Speciesmentioning
confidence: 99%